Designing, installing, and maintaining the colonial apparatus: the work of the organ-building firm, G.W. Price & Son - Hughes, Jonathan Edward (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMus)--Stellenbosch University, 2025.